Therapeutic Options and Drug Delivery System & Potential Herbal Molecules Forvitiligo Therapy - Sazid; Kumar, Rahul; Sharma, Mayank; Dixit, Chandrakant; Koranga, Bhawana (Journal of Biomedical and Pharmaceutical Research, 2023)
Vitiligo is a condition in which the skin start to lose its pigmentation that appear to be white patches on the skin, the mechanism of vitiligo is still under investigation but some of the hypothesis suggest that it is an autoimmune disease in which amount of melanine is reduced in certain areas of the skin.Various biomarkers have been identified by the scientists that help in the assessment of this disease which further help in the treatment of this disease. Many herbal drugs are proven to be effective in the treatment of vitiligo for example; Ashwagandha, Black Cumin, Barberry Root etc. many of the herbal products of these and other plants are available in the market like  Anti-leucoderma oil, Ayurhealthline capsules, Ayurhealthline cream, Pigmento cream.